(untitled) (Revista de Ciências Agroveterinárias, 2006)
Ethnobotany, ethnopharmacology and other discipline s with ethno (ethnos) are interdisciplinary sciences. Despite the seeming acc eptance of the interdisciplinary concept in theory, in practice some academics seem to have trouble analyzing and incorporating data coming from anthropological observation. Ethnomethodological research involves the observation and registration of folk wisdom regarding the propertie s and use of medicinal plants. This body of traditional knowledge is tied to a community worldv iew. If these are separated (the knowledge and the communal weltanschauung), we run the risk of reductionism. Nevertheless, it is not uncommon that these factors are not taken into consideration when developing a new herbal medication or treatment.